Analytical method of fault characteristic and non-unit protection for HVDC transmission lines - Chu, Xu; Song, Guobing; Liang, Jun (CSEE Journal of Power and Energy Systems, 2016)
An analytical method of fault characteristic for the HVDC system based on frequency response characteristics of boundary elements is presented here. The computational formulas of transfer function and input impedance are deduced using the distributed parameter model of HVDC transmission line, and the amplitude-to-frequency-characteristics of the transfer function and input impedance are analyzed. Based on the amplitude-to-frequency difference between internal and external faults, a non-unit protection method for VSC-HVDC transmission line is presented. Using the current ratio of high-to-low-frequency, this protection method can distinguish internal from external fault. The presented algorithm only uses local-end current, has high operation speed, and is easy to implement. Simulations on a ±200 kV VSC-HVDC system are conducted to demonstrate the validity and feasibility of the developed protection method.